Challenges Of Educational Autonomy In The Implementation Of School-Based Management - Juniar, Cut Maulinda; Prasetyo, Muhammad Anggung Manumanoso (Universitas Islam Indonesia, 2025)
The implementation of School-Based Management (SBM) in educational institutions is expected to be carried out in accordance with established regulations. However, in practice, it often falls short of expectations. Common problems include limited budgets, inadequate facilities and infrastructure, low-quality human resources, and insufficient integration of educational technology. This study specifically aims to analyze the challenges of educational autonomy within the framework of SBM. A qualitative approach with a descriptive survey method was employed. The research was conducted at SMP Negeri 3 Muara Batu, with data collected through interviews and observations. The informants consisted of the school principal and several individuals directly involved in managing SBM. Interviews were conducted online via the WhatsApp application to adapt to field conditions, while observations were carried out at the school to examine both the implementation process and the progress achieved after adopting SBM. The findings indicate that the school has implemented programs designed to improve institutional quality. Through the application of SBM, the school strives to become more effective by exercising educational autonomy. Moreover, the study highlights that an effective school must incorporate efficient elements to enhance not only the institution’s overall quality but also the professional competence of teachers.